Manfaat dan Usulan Penerapan Quality Control Circle (QCC) pada Industri Penerbangan di Indonesia: A Literature Review - Tampilang, Steven; Anggraini, Farida Rahma; Purba, Humiras Hardi (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
Quality Control Circle (QCC) is a routine activity that is carried out systematically in various manufacturing industries by employees in the department, which is a demand from the current conditions of the manufacturing industry which are currently developing in various industries. Quality products in accordance with applicable regulations can overcome problems regarding quality, which is an action to improve quality aimed at increasing competition in gaining consumer loyalty. The purpose of this article is to explore the benefits and proposals for implementing QCC or what is known as the quality control group, which is a method to improve product quality, productivity and reduce product defects in various industries to provide recommendations to the aviation industry in Indonesia. Writing articles in this study by conducting literature reviews from international journals and national journals in various industries, by collecting and analyzing then concluding as many as 21 journals published in 2010 to 2023 regarding the implementation of QCC. Journals that have been collected are then analyzed by looking for research objectives and results then drawing conclusions from various journals, with analysis of literature reviews that can improve product quality, productivity, and reduce product defects in various industries so that researchers recommend the application of the QCC method in the aviation industry based on on a literature review.